River Studies in Northern Canada: Reading the Record from River Morphology - Church, Michael (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1977)
Summary Proposals for resource developments in northern Canada have generated a demand for rapid improvement in knowledge of northern hydrology and river processes. The regimen of northern rivers and aspects of northern river behaviour are discussed, emphasis being given to description of reconnaissance techniques used to develop rapidly information on these subjects. Some special techniques evolved in the course of recent studies in northern Canada are reviewed.